Isolation and analysis of endophytic microorganisms in wheat (Triticum aestivum L.) leaves - Larrán, Silvina (2002)
The present investigation was undertaken in order to select the surface-sterilization technique most efficient for eliminating epiphytes, to document the spectrum of endophytes of healthy leaves from three wheat cultivars in Buenos Aires Province (Argentina) and to determine their infection frequencies at three growth stages. Surface-sterilization with undiluted commercial solution of sodium hypochlorite was reaffirmed as adequate for removing epiphytes on wheat leaves. From the 450 wheat leaf segments incubated, three bacterial isolates and 130 fungal isolates were obtained. From all the isolates, 19 fungal species were identified. Bacterial isolates were characterized as Bacillus sp. There were significant differences between microorganisms, stages of growth, and stages × microorganisms interaction. Differences between cultivars, stages × cultivars, microorganisms × cultivars and for the triple interaction were not significant. Frequency of microorganisms isolated increased with crop age, but it was statistically similar for the three wheat cultivars tested (Klein Centauro, Klein Dragon and Buck Ombu). Rhodotorula rubra, Alternaria alternata, Cladosporium herbarum and Epicoccum nigrum were isolated in the highest frequency. The other microorganisms were present at intermediate or low values. The species isolated may be assigned to three groups: (a) well-known and economically important pathogens of wheat, (b) commonly abundant phylloplane fungi considered to be primary saprobic and minor pathogens and (c) species occasionally present in wheat.